HUBUNGAN KAUSAL KUALITAS LAYANAN, LOYALITAS DAN KOMITMEN NASABAH PADA BANK-BANK TOP BRAND 2007 DI YOGYAKARTA - Astuti, Widhy Tri (University of Merdeka Malang, 2008)
This research aimed to test a structural model describing the causal relationship ofservice quality, loyalty and commitment. The sample was drawn by a purposive samplingmethod. Data analysis was conducted by means of structural equation modelling with a programapplication of AMOS. The result of model evaluation with several criteria of goodness of fitindices results was made based on theories indices. The model was accepted. Several insightsemerge from our research: service quality affect service quality and commitment, althoughnot all relationships are direct, it means that loyalty as mediator variable to commitment.